2020
DOI: 10.51380/gujr-36-02-03
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Role of Employees Job Engagement for Relation of Emotional Labor With Life Satisfaction

Abstract: Considering the role of life satisfaction of an employee’s as vital factor for employees' performance which directly affects the firms' success, this study explores the role of emotional labor as an antecedent of life satisfaction via mediating role of the job engagement of bank officers working in private and public banks of Pakistan. The sample of 314 employees of officer rank 314 employees of banking sector are selected randomly for data collection. Results of cross-sectional data of 314 employees working i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Particularly in Europe, the majority peoples are dissatisfied from their level of the lives. According to Akhter, Kayani & Tahir, (2020) suggested that the dissatisfaction of life is being found more among the people with low level of income. In China researchers such as Taris, Beek and Schaufeli (2020) found that old age peoples are also highly dissatisfied from their lives.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly in Europe, the majority peoples are dissatisfied from their level of the lives. According to Akhter, Kayani & Tahir, (2020) suggested that the dissatisfaction of life is being found more among the people with low level of income. In China researchers such as Taris, Beek and Schaufeli (2020) found that old age peoples are also highly dissatisfied from their lives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It does not only motivate the employees to work with the high care and effectively but also encourage them to accomplish the high-valued tasks to gain the highest achievements. Life satisfaction is also considerable the emotional response of employees about their free time and their lives (Chung, & Kim, 2017;Akhter et al,, 2020). That's why the life satisfaction is very important for every organization.…”
Section: Life Satisfactionmentioning
confidence: 99%